Pengaruh Pengembangan Karir Dan Pelatihan Kerja Terhadap Kinerja Pegawai Dengan Motivasi Kerja Sebagai Variabel Intervening Pada Puskesmas Pakan Rabaa Kab. Lima Puluh Kota - Tri Shalbi Mardinata; Yulasmi Yulasmi; Chintya Ones Charli (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2025)
This study aims to analyze the influence of career development and job training on employee performance, with work motivation as an intervening variable, at the Pakan Rabaa Community Health Center in Lima Puluh Kota Regency. The background of this study is based on the importance of improving the quality of human resources through career development strategies and targeted job training programs, as well as the role of work motivation as a driving factor for employee performance. The research method used is Structural Equation Modeling (SEM) with the Partial Least Square (PLS) approach. Data were collected through distributing questionnaires to 66 respondents who are employees of the Pakan Rabaa Community Health Center. The results of the study show several important findings. First, career development has a positive and significant effect on work motivation. Second, job training has a positive but insignificant effect on work motivation. Third, career development has a positive but insignificant effect on employee performance. Fourth, job training has a positive and significant effect on employee performance. Fifth, work motivation has a positive but insignificant effect on employee performance. Sixth, career development has a positive but insignificant effect on employee performance through work motivation as an intervening variable. Seventh, job training also had a positive but insignificant effect on employee performance through work motivation as an intervening variable. This finding indicates that although career development and job training have a positive relationship with performance, the effect is not always significant when mediated by work motivation. Other factors beyond work motivation may also influence employee performance at the Pakan Rabaa Community Health Center. This study recommends that management strengthen career development and job training programs relevant to employee needs, while identifying other motivational factors that can further enhance performance.